2019
DOI: 10.1002/hed.25734
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of narrow band imaging with magnifying endoscopy for the differential diagnosis of cancerous and noncancerous laryngeal lesions

Abstract: Background We evaluated the accuracy of endoscopic findings observed by narrow band imaging (NBI) combined with magnifying gastrointestinal endoscopy (GIE) for the differential diagnosis of cancerous and noncancerous laryngeal lesions. Methods A total of 166 vocal cord lesions for which good images were obtained on NBI with magnifying GIE were evaluated with respect to the following 6 variables: macroscopic type, tumor location, color, white coat, keratinization, and abnormal microvessels. Results Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The results obtained in group A are in accordance with those reported in literature with a similar cohort of patients [1,9,10]. In particular, Vilaseca et al [1] showed that accuracy improved from 74.1% with WLE to 88.9% with NBI and demonstrated additionally, a better PPV (NBI: 89% vs. WLE: 74%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained in group A are in accordance with those reported in literature with a similar cohort of patients [1,9,10]. In particular, Vilaseca et al [1] showed that accuracy improved from 74.1% with WLE to 88.9% with NBI and demonstrated additionally, a better PPV (NBI: 89% vs. WLE: 74%).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, NBI is widely used for inflammatory pathologies of the head and neck in all age groups [7,8]. However, a precise diagnosis of mucosal lesions remains challenging and recent studies aimed at assessing its diagnostic accuracy in laryngeal lesions [9,10]. Considering the wide application of NBI in the head and neck area and the difficulties encountered by the physician with the number of different pathologies affecting these structures, the aim of our study was to assess the accuracy of NBI based on the differential diagnosis of laryngeal premalignant lesion, early cancers and tumor recurrences after radiotherapy in a large case series and single institution.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the sensitivities reported in this study were based on three expert assessments of still NBI and WLE images, not histopathological diagnosis. Recently, Hosono and colleagues 23 further reported a sensitivity of 84.4% using NBI even with high definition magnifying endoscopy. Although this is a higher sensitivity relative to Piazza et al 21 and Shoffel‐Havakuk et al, 22 it is much lower than the pooled sensitivity reported by Sun et al 18 …”
Section: Discussionmentioning
confidence: 97%
“…Two reviewers summarized all data using standard forms. The diagnostic odds ratios (DORs), 4‐31,35‐37 summary receiver operating characteristic (SROC) curves, areas under the curves (AUCs), 4‐31,35‐37 and the extent of inter‐rater agreement 17,22,23,26 associated with NBI studies were evaluated, as was the (comparative) diagnostic accuracy of WLE. Each DOR was calculated as: (true positive (TP)/false positive [FP])/(false negative [FN]/true negative [TN]) with 95% confidence intervals (CIs); we used random‐effects models that considered both within‐ and between‐study variations.…”
Section: Methodsmentioning
confidence: 99%